Much in Little: The Umbrella Clause that Changes the International Investment Protection Standard - Paramita, Kartika (Hasanuddin Law Review, 2020)
The umbrella clause of a Bilateral Investment Treaty (BIT) establishes an obligation for the State parties to respect all commitments entered into by an investment contract between an investor and the host country. It extends the jurisdiction of a BIT forum to the breach-of-contracts matters and changes the nature of a private issue to an international affair. The polemic over the clause's interpretation has become a controversial issue over the years. It comes as a backlash for the Contracting States as a foreign investor could quickly bring an investment problem to an international forum. After more than a decade since its first discussion in the case of SGS v Pakistan, the clause grows to be one of the reasons for many countries to leave or reform their BIT model and changes the trend of international investment protection standard. This article addresses the different episodes of the umbrella clause alongside over the past decade. It projects the debate over the clause’s scope, its development, the governments' action, and their perception over it, and finally, how it changes the standard of investment protection in international treaties.